If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -12 = 3x + 8 Reorder the terms: -12 + -6x = 3x + 8 Reorder the terms: -12 + -6x = 8 + 3x Solving -12 + -6x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + -6x + -3x = 8 + 3x + -3x Combine like terms: -6x + -3x = -9x -12 + -9x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + -9x = 8 + 0 -12 + -9x = 8 Add '12' to each side of the equation. -12 + 12 + -9x = 8 + 12 Combine like terms: -12 + 12 = 0 0 + -9x = 8 + 12 -9x = 8 + 12 Combine like terms: 8 + 12 = 20 -9x = 20 Divide each side by '-9'. x = -2.222222222 Simplifying x = -2.222222222
| 3y-2=2.26 | | 3(x+5)-2x+12= | | 7(314)-75(21)-2(259)=x(10+5) | | -2.22=m/4-5 | | 3[z-(6z+15)+5]=3(z+2) | | 1.3+2.3=2.3-2.3 | | Y+6+y=28 | | 7(314)-75(21)-2(259)=x(3+5) | | 1.2=4s-11.2 | | -7(x-8)=9-6x | | 11w-81=744 | | -8-5n=64+3 | | -2y^2-14y+7=0 | | 8[5-8(x-1)]+7[(5x+6)-8]=11x-341 | | .8=ln(y) | | 0=x^2+2x-63 | | 4x+4x=7x-9 | | 5y(y-2)=6-3y | | 4.7x+2=3.2x-4 | | 40x+4(1.5x)=736 | | 4(x-6)-(x+2)=-12 | | g/6-17=1 | | 4x-3+2=8x-3-x | | -8+2x=4 | | 16=10-1/4m | | graphy=-x^2+4x-7 | | 3(x+2)=4(x-7) | | g/30-980=-954 | | 3t(t-2)=4-2t | | -4(-2t-4)=-2[2t+3(t+2)] | | (1/7)-n/3=N? | | (1/7)-n/3= |